2020
DOI: 10.1093/braincomms/fcaa199
|View full text |Cite
|
Sign up to set email alerts
|

Amplified engagement of prefrontal cortex during control of voluntary action in Tourette syndrome

Abstract: Tourette syndrome is characterised by ‘unvoluntary’ tics, which are compulsive, yet often temporarily suppressible. The inferior frontal gyrus (IFG) is implicated in motor control, including inhibition of pre-potent actions through influences on downstream subcortical and motor regions. While tic suppression in Tourette Syndrome also engages the IFG, it is unclear whether such prefrontal control of action is also dysfunctional: Tic suppression studies do not permit comparison with control groups, and neuroimag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 63 publications
0
49
0
Order By: Relevance
“…Rae and colleagues provide a high-quality study of action inhibition in TS comprising 23 adults with TS and 21 healthy controls using the same intentional inhibition task ( Rae et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rae and colleagues provide a high-quality study of action inhibition in TS comprising 23 adults with TS and 21 healthy controls using the same intentional inhibition task ( Rae et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rae and colleagues provide a high-quality study of action inhibition in TS comprising 23 adults with TS and 21 healthy controls using the same intentional inhibition task (Rae et al 2020). Importantly, the authors chose a task that did not directly involve tics, so both groups could participate equally in inhibiting a movement.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…Of note, in this study self-paced voluntary actions (e.g., wrist extensions) in people with primary tic disorders were preceded, like in healthy control participants, by regular readiness potentials ( van der Salm et al, 2012 ). Indeed, the execution of voluntary actions, as well as reaction times in basic Go/NoGo paradigms in people with TS typically fall within the normal range of motor behavior ( Rae et al, 2020 , Thomalla et al, 2014 ). These results allow to draw several important conclusions often missed in the pathophysiological discussion of tics.…”
Section: Ticsmentioning
confidence: 99%
“…Of relevance to the present discussion, several studies have shown that tic suppression and cognitive control of motor behaviour are underpinned by the activation of the prefrontal cortex (PFC). [130][131][132] Interestingly, the relationship between tic severity and waiting impulsivity is mediated by connectivity between the orbitofrontal cortex (a subregion of the PFC particularly susceptible to the adverse effects of stress) and the caudate nucleus. 107…”
Section: Neurobiological Mechanisms Of Ticsmentioning
confidence: 99%